Em busca de uma proposição metodológica para os estudos das cidades médias: reflexões a partir de Uberlândia (MG) - Oliveira, Hélio Carlos Miranda de (2008)
This paper has like objective to do a methodological proposal in order to contribute in the studies of middle cities, getting like fundament methodologies already existent. In order to get this goal was made a rescue of four important papers in Brazilian s Geography, of two governmental studies and two foreign experiences, focusing in their texts the methodological ways made by them. These papers, with the methodological model followed for the Uberlândia City (MG) study, justified the methodological proposal worked in this paper. The study of economics Uberlândia City dimension allowed us to understand the place of economics agents in the transformation of the inside space of town and in the establishment of its fluxes chains, besides to work like an example for a proposition of a methodological study of middle cities. Was from this knowledge of the studied city reality, that some appointments were possible, being their relating to a new methodology or to a critique among the methodology used in this study. Then, in front of the regional context of Brazilian South-Center and the reality of Uberlândia City (MG), was made a methodological proposition organized in dimensions of the space s analysis, their variables and appointments. The dimensions brought in this paper are: demography, economy, of equipments and infra-structures, policy and territorial administration, environmental, social and cultural, besides of and typology for the Brazilian s middle cities. This new methodology is not over, with the new arguments done, it is a primary proposal which needs to be put under critiques, and, in this way could be used in future like reference for studies about Brazilian s middle cities.